Co-designing a nature-based intervention to promote postnatal mental health for mothers and their infants: a complex intervention development study in England - Richard Brown; Paul Moran; Katrina M Turner; Jonathan Evans; Katherine Hall; Christopher Barnes; Rosa Roberts; Lucy Duggan; Melanie Williamson (BMJ Open)
Objectives There is burgeoning evidence for the potential of nature-based interventions to improve wellbeing. However, the role of nature in enhancing maternal mental health, child development and early relationships remains relatively unexplored. This study aimed to develop a co-designed nature-based intervention to improve postnatal mothers’ and infants’ wellbeing.Design, setting and participants Person-based and co-design approaches informed the planning and design of the postnatal nature-based intervention. In stage 1, a multidisciplinary team was formed to agree research questions and appropriate methodology, and a scoping review was conducted. Six qualitative focus groups were then held with 30 mothers and 15 professional stakeholders. In stage 2, intervention guiding principles and a logic model were developed, and a stakeholder consensus meeting was convened to finalise the prototype intervention. The research was conducted in Bristol, UK, across voluntary, educational and community-based healthcare settings.Results Stakeholder consultation indicated significant enthusiasm for a postnatal nature-based intervention. A scoping review identified little existing research in this area. Focus group data are reported according to four broad themes: (1) perceived benefits of a group postnatal nature-based intervention, (2) potential drawbacks and barriers to access, (3) supporting attendance and implementation, and (4) ideas for intervention content. The developed intervention was tailored for mothers experiencing, or at risk of, postnatal mental health difficulties. It was identified that the intervention should facilitate engagement with the natural world through the senses, while taking into account a broad range of postnatal-specific practical and psychological needs.Conclusions To our knowledge, this is the first reported use of person-based and co-design approaches to develop a postnatal nature-based intervention. The resulting intervention was perceived by target users to address their needs and preferences. Further research is needed to determine the feasibility, clinical and cost-effectiveness of this approach.